Block Storage Migration in Open Environments - Anderloni, Francesco; DiVito, Matthew; Dufrasne, Bertrand; Eriksson, Roger; Moore, Christopher; Oscheka, Markus; Simpson, Duncan; Solewin, Stephen (IBM Redbooks, 2020)
Companies need to migrate data not only when technology needs to be replaced, but also for consolidation, load balancing, and disaster recovery (DR). Data migration is a critical operation, and this book explains the phases and steps to ensure a smooth migration. Topics range from planning and preparation to execution and validation. The book explains, from a generic standpoint, the appliance-based, storage-based, and host-based techniques that can be used to accomplish the migration. Each method is explained through practical migration scenarios and for various operating systems. This publication addresses the aspects of data migration efforts while focusing on fixed block storage systems in open environment with the IBM® FlashSystem 9100 as the target system. Therefore, the book also emphasizes various migration techniques using the Spectrum Virtualize built-in functions. This document targets storage administrators, storage network administrators, system designers, architects, and IT professionals who design, administer or plan data migrations in large data Centers. The aim is to ensure that you are aware of the current thinking, methods, and products that IBM can make available to you. These items are provided to ensure a data migration process that is as efficient and problem-free as possible. The material presented in this book was developed with versions of the referenced products as of February, 2020.